Differences in COVID-19 testing perceptions among caregivers of children with medical complexity by rurality - Kristina Devi Singh-Verdeflor; Michelle M. Kelly; Gregory P. DeMuri; Gemma Warner; Sabrina M. Butteris; Mary L. Ehlenbach; Barbara Katz; Joseph A. McBride; Shawn Koval; Ryan J. Coller (PLoS ONE, 2025)
Background COVID-19 testing safeguards the health of children with medical complexity (CMC) through several key mechanisms, such as the implementation of clinical action plans and COVID-19-directed therapies. However, testing utility is limited by barriers to access and perceptions surrounding use. This study investigated associations between rurality and COVID-19 testing access, intent, motivators, and concerns for caregivers of CMC. Methods We conducted a cross-sectional survey (April – June 2022) of English- and Spanish-speaking caregivers of children with at least one complex chronic condition between ages 5–17 at an academic medical center in the Midwestern USA. Rurality was dichotomized using Rural-Urban Commuting Area codes. Outcomes represented COVID-19 testing access, intent, motivators, and concerns. Covariates included demographic and clinical characteristics. Unadjusted and adjusted logistic regression analyses examined associations between rurality and each outcome. Results Among 1,432 responses (response rate 49%), 359 (25%) were classified as rural. Respondents had varied education, income, and insurance levels. In the multivariable models, rural and urban caregivers reported similarly high testing access, but rural caregivers had significantly less testing intent (adjusted Odds Ratio [95% CI]: 0.53, [0.40, 0.71]). Notably, rural caregivers were significantly more likely to indicate “It will be difficult to get needed healthcare if my child has it” (2.49 [1.19, 5.18]). Conclusions While rural and urban CMC caregivers reported generally high access and ease of COVID-19 testing, potentially modifiable factors exist to improve testing intention and decrease barriers, including communication regarding testing utility and timing as well as access to effective treatment response upon testing positive.